Transition Program Redesign for Cardiac Congenital Patients - Emily K. Gobble (My University, 2024)
Congenital heart patients experience physical, mental, social, and financial stressors throughout their lifetime. Evidence-based practice supports congenital heart patients participating in a transition program to increase their heart health competency and independence as they grow into adulthood. Historically, most established transition programs are managed by pediatric cardiology under the directorship of the children’s hospital; however, one transition program was failing under this model. Process improvement was completed and a novel approach where the Adult Congenital Heart Disease (ACHD) program managed the transition program was created. Next, a quality initiative project compared the rates of documentation compliance before and after the process update for assessment and education topics. The results showed a significant increase in documentation compliance of both the assessment and education topics. These results showed that a transition program for congenital heart patients can be successful when managed by the adult congenital program. Limited research is available on the workflow models of congenital heart transition programs; therefore, the introduction of a novel approach is significant.
Keywords: Transition program; Congenital heart; Adult congenital heart disease; Transition Program Model; Transition assessment